Improvement of the geotechnical engineering properties of dune sand using a plant-based biopolymer named serish - Shabani, Khosro; Bahmani, Maysam; Fatehi, Hadi; Chang, Ilhan (Geomechanics and Engineering, 2022)
Recently, the construction industry has focused on eco-friendly materials instead of traditional materials due to their harmful effects on the environment. To this end, biopolymers are among proper choices to improve the geotechnical behavior of problematic soils. In the current study, serish biopolymer is introduced as a new binder for the purpose of sand improvement. Serish is a natural polysaccharide extracted from the roots of Eremurus plant, which mainly contains inulins. The effect of serish biopolymer on sand treatment has been investigated through performing unconfined compressive strength (UCS), California bearing ratio (CBR), as well as wind erosion tests. The results demonstrated that serish increased the compressive strength of dune sand in both terms of UCS and CBR. Also, wind erosion resistance of the sand was considerably improved as a result of treatment with serish biopolymer. A microstructural study was also conducted via SEM images; it can be seen that serish coated the sand particles and formed a strong network.
Keywords: Biopolymer; California bearing ratio; Dunes sands; Eco-friendly materials; Engineering properties; Soils improvement; Sustainable materials; Traditional materials; Unconfined compressive strength; Wind erosions; biopolymer; sand; SEM; soil improvement; sustainable materials; unconfined compressive strength